Eating Disorder Risk and the Role of Clothing in Collegiate Cheerleaders' Body Images - Torres-McGehee, Toni M. (National Athletic Trainers Association, 2012)
CONTEXT: With increased media coverage and competitive opportunities, cheerleaders may be facing an increase in eating disorder (ED) prevalence linked to clothing-related body image (BI). OBJECTIVE: To examine ED risk prevalence, pathogenic weight control behaviors, and variation in clothing-specific BI across position and academic status among collegiate cheerleaders. DESIGN: Cross-sectional study. SETTING: National Collegiate Athletic Association Division I and II institutions. PATIENTS OR OTHER PARTICIPANTS: Female collegiate cheerleaders (n = 136, age = 20.4 ± 1.3 years, height = 160.2 ± 8.1 cm, weight = 57.2 ± 8.3 kg). MAIN OUTCOME MEASURE(S): Participants self-reported height, weight, and desired weight and completed the Eating Attitudes Test. Body image perceptions in 3 clothing types (daily clothing, midriff uniform, full uniform) were assessed using sex-based silhouettes (body mass index = 18.3 kg/m(2) for silhouette 1, 23.1 kg/m(2) for silhouette 4). RESULTS: The ED risk for cheerleaders was estimated at 33.1%. However, when body mass index was controlled using backward stepwise logistic regression, flyers had greater odds (odds ratio = 4.4, 95% confidence interval = 1.5, 13.2, P = .008) of being at risk compared with bases, but no difference was noted between the base and back-spot positions (odds ratio = 1.9, 95% confidence interval = 0.5, 6.6, P = .333). A main effect of BI perceptions was seen (P < .001), with a significant interaction by clothing type (F(2,133) = 22.5, P < .001, η(2) = 0.14). Cheerleaders desired to be smaller than their perceived BIs for each clothing type, with the largest difference for midriff uniform (2.6 ± 0.8 versus 3.7 ± 0.9), followed by full uniform (2.7 ± 0.8 versus 3.5 ± 0.9) and daily clothing (2.8 ± 0.8 versus 3.5 ± 0.9). CONCLUSIONS: Cheerleaders, especially flyers, appear to be at risk for EDs, with greatest BI dissatisfaction when wearing their most revealing uniforms (ie, midriffs). Universities, colleges, and the national governing bodies of these squads need to focus on preventing eating disorders and BI dissatisfaction and promoting self-esteem.